2013
DOI: 10.1136/bjsports-2013-092175
|View full text |Cite
|
Sign up to set email alerts
|

The experience of breast pain (mastalgia) in female runners of the 2012 London Marathon and its effect on exercise behaviour

Abstract: Mastalgia was experienced by a third of marathon runners and was found to be related to breast size which has previously been unreported. The link between exercise and mastalgia has yet to be established; however, this study identified that exercise was the most prevalent factor in mastalgia occurrence which may have implications for its management. The number of participants who took no measures to relieve their mastalgia, or resorted to pain medication, highlights the importance and significance of research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 39 publications
5
53
1
17
Order By: Relevance
“…Due to these negative consequences, previous research has recommended the use of external breast support. External breast support, such as sports bras, has been reported to reduce breast pain (Brown, White, Brasher, & Scurr, 2014), reduce embarrassment and alter performance variables (Shivitz, 2002; during running. Despite these recommendations, recent research has shown that only 32% of UK adult females always wore a sports bra during physical activity (Brown, Burnett, & Scurr, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Due to these negative consequences, previous research has recommended the use of external breast support. External breast support, such as sports bras, has been reported to reduce breast pain (Brown, White, Brasher, & Scurr, 2014), reduce embarrassment and alter performance variables (Shivitz, 2002; during running. Despite these recommendations, recent research has shown that only 32% of UK adult females always wore a sports bra during physical activity (Brown, Burnett, & Scurr, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Limited research has focused on factors associated with breast pain. Cyclic breast pain has been associated with hormone changes during the menstrual cycle and general breast pain has been associated with excessive breast movement increases in breast size, body mass index, and activity level . However, associated factors have not been investigated in the general population.…”
mentioning
confidence: 99%
“…In addition, pain was rated as mild (26%), moderate (59%), and severe (15%), with 93% reporting pain for greater than 5 days in each menstrual cycle. In a sporting population, Brown et al (7) identified that over half of symptomatic participants described the severity of breast pain as discomforting, yet 44% had done nothing to relieve their symptoms. Research into treatments for breast pain are limited; pain killers, and/or breast support are the most common recommendations (8,9).…”
mentioning
confidence: 99%
“…The meta-analysis by Luo4 examining physical activity and the risk of gestational diabetes mellitus (GDM) broadens our understanding of the mechanisms by which activity can prevent GDM. Finally, Dr Nicola Brown5 addresses mastalgia (breast pain) a little known problem faced by endurance athletes, and how it impacts their participation. Clinicians need to be proactive in assessing this type of breast pain as part of the preparticipation evaluations, and when considering dropout from sport.…”
Section: Female Athlete Triad and More…mentioning
confidence: 99%